PENGEMBANGAN E-LKPD BERBASIS KOMIK DIGITAL UNTUK MENINGKATKAN PEMAHAMAN TEKS NARASI PADA SISWA KELAS IV SD (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In a primary school in Malang City, teachers tend to underutilize technology and rely on monotonous teaching materials. As a result, the learning process becomes less effective, students quickly get bored, and their ability to write narrative texts in a structured and engaging way continues to decline. The purpose of this study is to assess the validity, practicality, and effectiveness of a digital comic-based E-LKPD (Electronic Student Worksheet) in teaching Indonesian language and narrative text material for elementary school students. This research uses a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data collection techniques in this study include questionnaires and tests, product validation sheets, as well as questionnaires for teachers and students. Data analysis was conducted using both qualitative and quantitative methods. Based on the results of the media expert assessment, the percentage was 96.87%, the material expert assessment was 93.33%, and the language expert assessment was 100%, resulting in an average of 96.74%, categorized as “very valid.” The results from the practicality test for teachers yielded 98.21%, while the limited trial with students obtained 92.81%, and the large-scale trial resulted in 95.19%, all categorized as “Very Practical.” In terms of effectiveness, the N-Gain score was 0.7, categorized as “High,” and in percentage terms, it was 75.85%, categorized as “Effective,” indicating that this media is effective in improving students' understanding of narrative texts. Therefore, it can be concluded that the use of the digital comic-based E-LKPD is valid, practical, and effective as an interactive teaching material and can enhance elementary students’ understanding of narrative texts.